Three patients with 46, X, inv(Y)(p11.2q11.2)pat/45, X and their pedigree analysis. (12th March 2020) - Chen, Yunchun; Xu, Yuni; Cao, Xiaoqiang; Zheng, Chunqiao; Lin, Liying; Zhu, Zhongyuan; Hu, Jiandong
Abstract: The present study aimed to perform chromosome examination and pedigree analysis on three patients with semen abnormality who had undergone in vitro fertilization–embryo transfer (IVF‐ET). Peripheral blood cell culture and chromosome karyotyping were performed on 4, 200 individuals who had undergone chromosome examination. Among them, 155 pregnant women who had successfully conceived were subjected to amniotic cell culture and chromosome karyotyping and those with abnormal chromosome karyotype were further subjected to C‐banding and whole‐genome sequencing. Mosaicism for a 46, X, inv(Y)(p11.2q11.2)pat/45, X karyotype was identified in the probands and immediate adult male relatives. The incidence of this mosaicism in the study population was only 0.07% (3/4, 200), which is reported for the first time. For the proband of pedigree A, the results of whole‐genome sequencing and other tests were normal, and the chromosome karyotype of IVF fetuses was 46, X, inv(Y)(p11.2q11.2)pat. All the male members of three pedigrees have normal phenotypes, with no features of Turner's syndrome (45, X) or hermaphroditism (45, X/46, XY), suggesting that the inverted Y chromosome is extremely unstable and particularly susceptible to loss in somatic cells. So we speculate this karyotype may be a unique type of inverted Y chromosome in somatic cells.